The storytelling human : Lithuanian folk tradition today - Būgienė, Lina, 1968- (Boston : Academic Studies Press, 2020)
"This book is among the very few publications offering to the English-speaking readership significant insights into contemporary Lithuanian folklore research. Dealing with broad variety of materials-from archived manuscripts to audio-recorded life stories to internet folklore, it comprises such topics as history and identity, traditional worldview influencing modern people's actions, construction of the mental landscape, types and modes of storytelling, the modern uses of proverbs, anecdotes, and internet lore. In a balanced way reflecting upon past and present, tradition and modernity, individual and collective, and employing modern research methodologies to dissect and analyze popular subjects and themes, the eight separate essays comprising the book present a condensed view of the popular Lithuanian culture and mentality"--
Predominant modes of perception and folk narrative / Aelita Kensminienė -- Taking shelter in memoir amid turmoil of history : reconstructing mental landscapes in autobiographical narratives / Radvilė Racėnaitė -- The dead want to come home : stories about the repatriation of Siberian deportee remains to Lithuania / Daiva Vaitkevičienė -- Borderland lives : historical reflections in Eastern Lithuanian life stories / Lina Būgienė -- Life in folktales and folktales in life? : how storytellers influence traditions / Jūratė Šlekonytė -- The contemporary consumer and creator of proverbs, or why do we need proverbs today? / Dalia Zaikauskienė -- Homo ridens : the joking human in Lituania from the late nineteenth to the early twenty-first centuries / Salomėja Bandoriūtė -- Between culture and subculture : the case of Lithuania's basketball fans / Povilas Krikščiūnas.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Folklore -- Lithuania; Storytelling -- Lithuania; folkloristiikka; suullinen perinne; kertomusperinne; muistelmat; muistitieto; kerronta; sananlaskut; vitsit; osakulttuurit; Liettua